The Determination Of Local Malay Female Bone Mineral Density And Its Correlation With Geometric Properties In The Evaluation Of Skeletal Status. - MM, Abdul Kareem; Shuaib, Ibrahim Lutfi; Dr Lee, Cheng Wai; Ezane, Dr Mohd (2004)
To establish bone mineral density ( BMD ) reference data for local Malay female population and to determine the correlation of BMD and geometric properties Methoelology: A total of 137 Malay female volunteers who have given a written informed consent have undergone DEXA of the spine, dual femur and total body using LUNAR PRODIGY, GE Medical Systems.